2019
DOI: 10.1002/jcb.29021
|View full text |Cite
|
Sign up to set email alerts
|

The effect of GNAQ methylation on GnRH secretion in sheep hypothalamic neurons

Abstract: Kazakh sheep are seasonal estrous animals, and gonadotropin-releasing hormone (GnRH) is the key to fertility regulation. The nutritional level has a certain regulatory effect on estrous, and vitamin B folate plays a role in DNA methylation, directly participating in the process. The goal of this study was to determine whether folate is involved in GnAQ methylation and its effect on GnRH secretion. The hypothalamic neurons of Kazakh fetal sheep were treated with folate at concentrations of 0 mg/mL, 4 mg/mL, 40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…This concentration also upregulates the DNMT1 gene, which in turn stimulates the downregulation of GNAQ expression. Ultimately, this results in the indirect regulation of GnRH secretion, which affects the reproductive activities of sheep(Zhai et al, 2019).This study found that the GRM1, GNAQ and HCRTR1 genes have strong genotypic consistency in the sheep breeds of perennial oestrus and seasonal oestrus. However, the two types of populations are obviously different.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…This concentration also upregulates the DNMT1 gene, which in turn stimulates the downregulation of GNAQ expression. Ultimately, this results in the indirect regulation of GnRH secretion, which affects the reproductive activities of sheep(Zhai et al, 2019).This study found that the GRM1, GNAQ and HCRTR1 genes have strong genotypic consistency in the sheep breeds of perennial oestrus and seasonal oestrus. However, the two types of populations are obviously different.…”
mentioning
confidence: 70%
“…This concentration also upregulates the DNMT1 gene, which in turn stimulates the downregulation of GNAQ expression. Ultimately, this results in the indirect regulation of GnRH secretion, which affects the reproductive activities of sheep (Zhai et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The hypothalamic levels of GH-releasing hormone (GHRH), an important stimulator of somatotroph proliferation, were strongly decreased, which causes somatotroph hypoplasia, dwarfism, and anorexia in mice [61]. In a study of Kazakh sheep, it was also demonstrated that appropriate folate concentrations could promote GANQ promoter methylation, which in turn affected GnRH secretion and the growth of sheep [62]. It has also been suggested that, in humans, a primary effect of GNAQ variance on cAMP levels in the thyroid would affect the production of T4 and T3 and feedback to alter TSH release by the pituitary gland [63].…”
Section: Discussionmentioning
confidence: 99%
“…GNAQ mutations are found in a variety of diseases, including but not limited to: p.T96S NK/T cell lymphoma and diffuse bone and soft tissue angiomatosis ( Li et al, 2019 ; Gaeta et al, 2020 ); p.R183Q Klippel-Trenaunay syndrome ( He et al, 2020 ); p.V179M and p.F335L dark skin point mutations and hyperpigmentation ( Garcia et al, 2008 ; Van Raamsdonk et al, 2009 ; Jain et al, 2020 ); p.Q209L or silencing mutations in non-small cell lung cancers ( Choi et al, 2020 ); p.D663fs insertion and p.R385* nonsense mutations in melanocytoma ( Francis et al, 2016 ); p.Q209L and p.Q209P intramedullary and leptomeningeal melanomas ( Fortin Ensign et al, 2020 ); p.S12fs*49 breast cancer ( Schrader et al, 2016 ); and decreased GNAQ expression in brain aging and neurodegeneration ( Wettschureck et al, 2005 ; Frederick et al, 2012 ; Chen et al, 2017 ; Arey et al, 2018 ; Zhai et al, 2019 ; Sun et al, 2020 ). The following diseases discussed in more detail were selected due to the possible overlap in pathogenesis or molecular interactions, with the goal of spurring synergistic research encompassing these conditions and SWS.…”
Section: Overlap With Other Vascular Malformationsmentioning
confidence: 99%